Mapping Management Information System for Midwife Clinics in Batam City District - Fendi Hidayat; Dwi Ratna Fitriyani; Risqi Utami; Yoga Fitriana (Journal of Applied Geospatial Information, 2021)
Currently, there is no information system that provides information on the location of geographically integrated midwifery practices in the Batam City sub-district. the application of GIS can be done to map the location of the practice of midwives so that it can be used to find out the location of the practice, hours of service and other necessary information. This research uses descriptive research method and the system development method uses the waterfall method and the design model uses UML. With a mapping management information system developed using web technology so that it can provide information to the public at large